ANALISIS PENERAPAN SISTEM MANAJEMEN RANTAI PASOK BERBASIS WEB UNTUK MENINGKATKAN EFISIENSI PRODUKSI GULA AREN (STUDI KASUS: FAMILY GULA AREN KISARAN) - Tati Hidyati; Rizaldi; Sumantri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid development in the business world encourages the importance of implementing Supply Chain Management (SCM) to improve the efficiency and effectiveness of business operations. Family Gula Aren Kisaran, a business engaged in palm sugar production, faces various obstacles in supply chain management, such as delays in raw material supplies due to still relying on manual ordering processes through agents. Information irregularities and the absence of a computerized system also hamper the production process. This study aims to analyze the implementation of supply chain management at Family Gula Aren Kisaran and propose a web-based system. The results of the study indicate that the designed system is able to manage inventory, supplier, production, and distribution data more efficiently, improve data accuracy, and minimize the risk of errors due to information delays with an average transaction recording time of 4 seconds per transaction. With the implementation of this system, business operations become more coordinated and sustainable.